Tips for Conducting a Gender Analysis at the Activity or Project Level - Cozzarelli, Cathy (USAID, 2010)
I. What is gender analysis? II. Relevant sections of the ADS III. Proc ess – What should you do to collect the information you need to conduc t a gender analysis at the activity or project level? IV. What questio ns should you ask in the context of doing your gender analysis? - Acce ss - Knowledge, Beliefs, and Perceptions - Practices and Participation - Time and Space - Legal Rights and Status - Power and Decision-makin g IV. What should you do after you ask these questions?